PENYULUHAN TENTANG “AYO KUATKAN ANAK KITA DENGAN IMUNISASI WAJIB” DI PUSKESMAS KUTA BARO KABUPATEN ACEH BESAR - Saufa Yarah; Martina; Melia Benita; Maulida; Omi Sastika; Sri Eva Ridha (Transpublika Publisher, 2020)
Immunization is a process to form and increase the body's immunity against a certain infectious disease. The way to trigger immunity is by giving vaccines. Compulsory immunization is immunization that must be obtained by children before the age of 1 year. In Indonesia, there are 5 types of immunization that must be given to children. Each type of immunization needs to be given according to a schedule in order to provide a maximum protective effect against disease. Fulfillment of this mandatory immunization has proven to be safe and useful to protect children from disease while preventing disease transmission to other children. If at any time a child who has been immunized is infected, he usually shows milder symptoms than a child who is not immunized. Compulsory immunization can be obtained free of charge at the public health center which refers to puskesmas or posyandu because it has been budgeted for by the government. Meanwhile, additional immunizations can be obtained by paying a fee according to the price of the vaccine and the tariff for doctor services at certain immunization sites. The method used is Pre Test and Post Test using a questionnaire. Based on the results of the counseling there was an increase in respondents' knowledge of mandatory immunization, which was in the good category as much as 23 (53.49%). Likewise, there is a significant increase in respondents' knowledge after being given counseling. Based on the results of the counseling there was an increase in respondents' knowledge of mandatory immunization, which was in the good category as much as 23 (53.49%). The conclusion is that there is a significant increase in respondents' knowledge after being given counseling. In conclusion, there was an increase in respondents' knowledge of mandatory immunization, which was in the good category as much as 23 (53.49%) which reveal that there is a significant increase in respondents' knowledge after being given counseling.